IMPROVING THE READING COMPREHENSION OF THE EIGHTH YEAR STUDENT OF SMP 5 PINRANG THROUGH RAP (READ-ASK-PUT) STRATEGY - Nurhidayati; Jabu, Baso; Latifa, Ammang (La Parole : Journal of Language Teaching and Pedagogy, 2021)
This research is aimed to investigate whether Read-ask-put (RAP) Strategy improves significantly students’ reading comprehension. A quasi-experimental method was conducted in this research with a time-series design consisting of one pretest-posttest group. The population of this research was the student of class VIII SMP 5 Pinrang in the 2018/2019 academic year which consisted of 10 classes. The sample was taken by purposive sampling technique, VIII.1 class as the experimental group and VIII.2 as the control group. The number of experimental groups was 30 students and 30 students in the control group. The research instrument used was reading the test. Based on the data analysis, the mean score of the experimental group was higher than the controlled group (79,6> 72,76). This showed that the reading comprehension of the students who are taught through rap strategy was better than the students who are taught through reading aloud. The result of t-test value (3,07) was greater than t-table for α = 0.05 with df = 58 is 1.671. It means that the alternative hypothesis was accepted. The study concluded that teaching English through RAP Strategy improved the students’ reading comprehension in SMP 5 Pinrang.